Projeto e análise do fluxo de um túnel de água circulante horizontal - FONTANA, Arthur dos Reis Lemos (2022)
The school boat project developed by the Collaborating Center for School Transport Support and financed by the federal government was responsible for the design and production of boats that serve to guarantee the access of the riverside children to the schools. A grandiose project like this requires advances in the experimental studies of vessels' hooves. A circulating water tunnel is a perfect installation for various types of experiments involving boat hulls, propeller tests etc. Thus, to support academic activities as well as support research that needs to conduct experiments with continuous and uniform water flow, a circulating water tunnel was designed to be located in the NDAE shed, which is located on the university campus of Tucuruí . In addition, dynamic flow analysis via CFD was performed in order to minimize speed variations and to find the best design for directing fins, leaving the flow quality even better.